Atomic-scale surface of fused silica induced by chemical mechanical polishing with controlled size spherical ceria abrasives. (6th January 2023) - Xu, Guanghong; Zhang, Zhenyu; Meng, Fanning; Liu, Lu; Liu, Dongdong; Shi, Chunjing; Cui, Xiangxiang; Wang, Jianmei; Wen, Wei
Abstract: Fused silica is widely used in precision optical devices for its excellent optical properties. However, it has hard and brittle nature, becoming a difficult-to-process material. This makes microscopic cracks left on the processed surface of silica induced by traditional mechanical processing methods. In this regard, it is a challenge to achieve an atomic-scale surface on silica. To overcome this challenge, nanometer CeO2 abrasives with uniform shape and size were prepared via a hydrothermal method. A novel chemical mechanical polishing (CMP) slurry is developed using the prepared CeO2 abrasives, Na2 CO3 and deionized water, which is low-cost, non-toxic, and environmentally friendly. The surface roughness, Sa of fused silica after CMP is 0.093 nm with a scanning area of 20 × 20 μm 2 . To the best of our knowledge, it is the lowest surface roughness on silica after CMP. The CMP mechanism was investigated by X-ray photoelectron spectroscopy and infrared Fourier transformation. Under alkaline conditions, the abrasives interacted with the silica forming a CeOSi reaction product, through a chemical tooth action, which is significant to produce an atomic-scale surface on silica. These findings provide a new pathway to fabricate atomic-scale surface for a hard-brittle solid.